2022
DOI: 10.1177/13623613221080318
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of satisfaction with the detection process of autism in Europe: Results from the ASDEU study

Abstract: Satisfaction with the detection process of autism and its determinants was investigated using data from the Autism Spectrum Disorder in the European Union (2015–2018) network. A total of 1342 family members, including 1278 parents, completed an online survey collecting information about their experience and satisfaction with the early detection of autism in their child. Overall, the level of satisfaction varied considerably from one respondent to another. Difficulty in finding information about detection servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Added to this, once concerns were raised, a high percentage (62%) of respondents reported that it was not easy to access information about early detection services. This gap seems to be caused by lack of information and awareness about autism, early signs of autism, and services availability among the general population [ 20 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, once concerns were raised, a high percentage (62%) of respondents reported that it was not easy to access information about early detection services. This gap seems to be caused by lack of information and awareness about autism, early signs of autism, and services availability among the general population [ 20 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%